EFEKTIVITAS IMPLEMENTASI KEBIJAKAN DIGITALISASI PELAYANAN PUBLIK DALAM MENINGKATKAN KUALITAS LAYANAN ADMINISTRASI PEMERINTAH - Anintiya Salsabilla; Ferawaty Y. Molomo; Mutia Amain; Yunika S. Lasena; Moh. Zikal Habibu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effectiveness of implementing digitalization policies for public services in improving the quality of government administrative services. Digitalization of public services is one of the government's efforts to realize good governance through the use of information and communication technology. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through in-depth interviews, field observations, and documentation studies. The results show that the implementation of public service digitalization policies has had a positive impact on improving the quality of administrative services, characterized by increased service accessibility, time efficiency, and community satisfaction. However, there are still several obstacles such as limited technology infrastructure, low digital literacy among the public, and internal bureaucratic resistance. This study recommends strengthening digital infrastructure, increasing human resource capacity, and massive socialization to the public.